A heterogeneous population model for contagious bovine pleuropneumonia transmission and control in pastoral communities of East Africa - Mariner, Jeffrey C.; McDermott, John J.; Heesterbeek, J.A.P.; Thomson, G.; Roeder, P.L.; Martin, S.W. (Elsevier, 2006)
Pastoral cattle live in highly structured communities characterized by complex contact patterns. The present paper describes a spatially heterogeneous model for the transmission of contagious bovine pleuropneumonia (CBPP) developed specifically for pastoral communities of East Africa. The model is validated against serological data on the prevalence of CBPP infection in several communities of southern Sudan and against livestock owner information on community structure, livestock contact and cattle exchange. The model is used to assess the impact of alternative control strategies including mass and elective vaccination programmes, potential treatment regimes and the combination of vaccination and treatment in a single unified strategy. The results indicate that the eradication of CBPP using mass vaccination with currently available vaccines is unlikely to succeed. On the other hand, elective control programmes based on herd level vaccination, treatment of clinical cases or a combination of both vaccination and treatment enabled individual livestock owners to capture a large benefit in terms of reduced animal-level prevalence and mortality experience. The most promising intervention scenario was a programme which combined the vaccination of healthy animals with treatment of clinical cases.